Unemployment and Poverty on Indonesia’s Economic Growth in 2002-2022 - Pesireron, Auldry; Hahury, Hendri D.; Leasiwal, Teddy Ch. (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2025)
The capacity of a region or country to improve the well-being of its community reflects its economic growth and overall living standards. However, achieving sustainable economic growth requires monitoring macroeconomic factors such as poverty and unemployment, which significantly impact regional stability. This study, based on data from Statistics Indonesia, analyzed the relationship between these variables and economic growth using multiple linear regression. The findings suggest that unemployment does not significantly influence economic growth, indicating that its role in economic performance may be limited in this context. Conversely, poverty emerged as a critical factor with a significant impact on economic growth, highlighting its importance in shaping economic outcomes. Together, these variables underscore the need for focused efforts to maintain macroeconomic stability, particularly by addressing poverty, to achieve high and sustainable economic growth.